PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2013 - Monot Wicaksono; Paryanto Paryanto (ITB AAS INDONESIA, 2016)
This study aims to examine the causal relationship of corporate characteristics to corporate social responsibility disclosure on manufacturing companies listed in Indonesia Stock Exchange 2012-2013. This research uses secondary data that is company annual report obtained from www.idx.com and company website during period 2012-2013. The sample selection process is done by using cluster sampling method. The analysis method used is multiple regression analysis consisting of classical assumption test (normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test) and hypothesis test (coefficient of determination, t test, F test). The results of this study indicate that profitability, liquidity, company profile has no effect on CSR disclosure. F test results show that the independent variables simultaneously affect the dependent variable.